PERAN ORANG TUA DALAM PEMBELAJARAN MODEL DISTANCE LEARNING DI SEKOLAH DASAR KOTA JAYAPURA - Didik Efendi (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2020)
This research aimed to figure out the role of parents in assisting elementary students’ learning through a distance learning model in Jayapura and its problems faced by the parents. This qualitative research was conducted in Jayapura City, Papua Province. Data collection techniques of this research used interview and questionnaire which was distributed by using google form to the subjects. The findings showed that there were four roles of parents in assisting elementary students’ learning through a distance learning model, namely (1) Educator, meaning that the parents performed as a mentor and teacher of the children at home; (2) Motivator, meaning that the parents motivated their children continuously during distance learning model; (3) Facilitator, meaning that the parents provided facilities and conveniences for their children and provide various learning resources for their children; (4) Inspirator, meaning that the parents became a model for their children as they act as teacher. The problems faced by parents in a distance learning were (1) difficult to manage the time; (2) unstable network; (3) they fear a new technology (technophobe); (4) require patience; and (5) the way to provide assistance when the parents were at work.